Ib-AMP4 insertion causes surface rearrangement in the phospholipid bilayer of biomembranes: implications from quartz-crystal microbalance with dissipation - Fan, Xiaobo; Korytowski, Agatha Anna; Makky, Ali; Tanaka, Motomu; Wink, Michael (Biochimica et biophysica acta. Biomembranes, 2018)
Most antimicrobial peptides exert their rapid bactericidal activity through a unique mechanism of bacterial membrane disruption. However, the molecular events that underlie this mechanism remain partly unresolved. In this study, the frequency shift (ΔF) obtained through quartz-crystal microbalance with dissipation (QCM-D) indicated that the initial binding of Ib-AMP4 within the lipid membrane started at a critical Ib-AMP4 concentration that exceeded 100μg/ml. Circular dichroism measurements provided evidence that Ib-AMP4 occurs in a β-sheet configuration which is adapted for insertion into the lipid membrane. Monolayer experiments and the value of dissipation alteration (ΔD) obtained through QCM-D showed that the pressure increased within the phospholipid bilayer upon peptide insertion, and the increase in pressure subsequently forced the bilayer to wrinkle and form pores. However, D continued to increase, indicating that the membrane surface underwent a dramatic morphological transition: the membrane surface likely became porous and uneven as Ib-AMP4 projected from the external surface of the lipid bilayer. Intensive peptide insertion, however, soon plateaued 1min after the addition of Ib-AMP4. This behaviour corresponded with the results of bactericidal kinetics and liposome leakage assays. A sudden decrease in D accompanied by a negligible decrease in F occurred after replacing the Ib-AMP4 solution with HEPES buffer. This result implied that the bilayer surface rearranged and that poration and wrinkling decreased without further peptide insertion. Transmission electron microscopy results indicated that pore formation occurred during Ib-AMP4 insertion but eventually subsided. Therefore, the mode of action of AMP in bacterial membranes could be elucidated through QCM-D.